Identification of the protonation and oxidation states of the oxygen-evolving complex in the low-dose X-ray crystal structure of photosystem II - Saito, Keisuke; Nakao, Shu; Ishikita, Hiroshi (Frontiers in Plant Science, 2023)
In photosystem II (PSII), the O3 and O4 sites of the Mn4CaO5 cluster form hydrogen bonds with D1-His337 and a water molecule (W539), respectively. The low-dose X-ray structure shows that these hydrogen bond distances differ between the two homogeneous monomer units (A and B) [Tanaka et al., J. Am Chem. Soc. 2017, 139, 1718]. We investigated the origin of the differences using a quantum mechanical/molecular mechanical (QM/MM) approach. QM/MM calculations show that the short O4-OW539 hydrogen bond ( 2.5 Å) of the B monomer is reproduced when O4 is protonated in the S1 state. The short O3-NεHis337 hydrogen bond of the A monomer is due to the formation of a low-barrier hydrogen bond between O3 and doubly-protonated D1-His337 in the overreduced states (S−1 or S−2). It seems plausible that the oxidation state differs between the two monomer units in the crystal.